2022
DOI: 10.3390/md20020116
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Polysaccharides from Seaweed Strandings as Renewable Source for Potential Antivirals against Herpes simplex Virus 1

Abstract: Herpes simplex virus 1 (HSV-1) remains a prominent health concern widespread all over the world. The increasing genital infections by HSV-1 that might facilitate acquisition and transmission of HIV-1, the cumulative evidence that HSV-1 promotes neurodegenerative disorders, and the emergence of drug resistance signify the need for new antiviral agents. In this study, the in vitro anti-herpetic activity of sulfated polysaccharides (SPs) extracted by enzyme or hot water from seaweeds collected in France and Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 73 publications
(125 reference statements)
0
29
0
Order By: Relevance
“…Marine sulfated polysaccharides derived from red algae often possess marked anti-HSV activities, mainly through inhibiting virus attachment to cell surfaces ( Pliego-Cortés et al., 2022 ). The sulfation content is the key factor which influences the anti-HSV effects of other red algae derived polysaccharides.…”
Section: Anti-hsv Effects Of Natural Compounds Obtained From Marine O...mentioning
confidence: 99%
“…Marine sulfated polysaccharides derived from red algae often possess marked anti-HSV activities, mainly through inhibiting virus attachment to cell surfaces ( Pliego-Cortés et al., 2022 ). The sulfation content is the key factor which influences the anti-HSV effects of other red algae derived polysaccharides.…”
Section: Anti-hsv Effects Of Natural Compounds Obtained From Marine O...mentioning
confidence: 99%
“…In a recent work from Pliego-Cortés et al [147] the in vitro antiherpetic activity of sulphated polysaccharides extracted from seaweeds collected in France and Mexico from stranding events were evaluated. Results showed significant antiviral activity and no cytotoxicity exhibited from red alga Halymenia floresii.…”
Section: Anti-herpetic Activity Of Seaweedsmentioning
confidence: 99%
“…Broad antiviral spectrum [113,[156][157][158] In vitro/in vivo inhibition of virus replication [115,122,124] Enhanced antibody production and immunomodulation activity [127,165,189,190] Anti-inflammatory activity [167] Prevention of the virus entry into the host cell [126,131,149] RT inhibition potential [132][133][134]136] No cytotoxicity effect [128,143,147,149] Compounds can be included in prophylaxis treatments [131,148,169] Cons Antiviral activity depends on the chemical structure (e.g., low antiviral activity is given by low number of sulphated groups) [70,80,[98][99][100]142] Strong anticoagulant activity of carrageenan could provoke adverse reaction in antiviral treatments [97,126,175,186,187] Antiviral activity is influenced by extraction methods [133,134] Poor adherence/non-frequent use of seaweed-based treatment decreases antiviral activity [173] The use of natural compounds as a replacement for synthetic ones or in combination with pre-existing antiviral treatments could be a way to optimize the production cost of drugs, to reduce side effects in patients as seaweed's comp...…”
Section: Prosmentioning
confidence: 99%
“…Kappa-, lambda-, and iota-carrageenans also display antiviral properties, which have been demonstrated against several enveloped viruses including a wide range of respiratory viruses such as paramyxoviruses, respiratory syncytial virus (RSV), influenza viruses (FluV), and seasonal coronaviruses [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Recently, Pliego-Cortés et al (2022) demonstrated in vitro evidence of the antiviral activity of lambda- and iota-carrageenans extracted from stranding biomass of Halymenia floresii and Solieria chordalis against Herpes simplex virus 1 (HSV-1) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%